Economic inequality and congressional action in the United States: A comparison of the minimum wage and alternative minimum tax. Issue 3 (8th September 2021) - Koger, Gregory; Rodriguez, Stefanie
Abstract: A central puzzle in American politics is the stark increase in economic inequality since the early 1970s due, in part, to the absence of public policies to address this trend. One explanation is policy drift : Inequality has grown in the United States because the political process has been unresponsive to economic trends toward inequality. A second explanation is unequal political influence: Wealthy individuals and corporations wield superior political influence and tilt public policy toward their interests. We compare these explanations using the federal minimum wage and alternative minimum tax (AMT) from 1969 to 2012 as comparison cases. These policies were both denominated in nominal dollars, so the effect of policy inaction is comparable for both policy domains. We find that (1) the U.S. Congress was much more likely to update AMT policy than minimum wage policy after 1978, (2) Congress protected and increased the real value of the AMT deduction for married couples, whereas the real value of the minimum wage and individual deduction declined after 1978, (3) Congress and the President eventually converted the AMT—but not the minimum wage—to automatic adjustments for inflation. These patterns highlight the role of political inequality in economic policy‐making. 摘要: 美国政治中的一个关键难题是1970年以来经济不平等的显著增加，这部分归因于缺乏能应对该趋势的公共政策。一种解释是政策偏移（policy drift）：美国不平等趋势的增加是因为政治过程一直不响应经济不平等趋势。另一种解释则是不平等的政治影响：富裕的个人和公司发挥更高的政治影响，并将公共政策向自身利益倾斜。通过将1969‐2012年间的联邦最低工资和替代性最低税（AMT）作为比较案例，我们比较了这两种解释。联邦最低工资政策和替代性最低税政策都以名义美元为单位，因此政策不作为（policy inaction）产生的效果是可比较的。我们发现，(1) 1978年后，美国国会更有可能更新AMT政策，而不是最低工资政策，(2) 1978年后，国会保护并提高了AMT减免对已婚人士的真正价值，但最低工资的真正价值和个人AMT减免却降低了，(3) 国会和总统最终让AMT（而不是最低工资）随通胀情况而自动调整。这些模式强调了政治不平等在经济决策中的作用。 Resumen: Un enigma central en la política estadounidense es el marcado aumento de la desigualdad económica desde principios de la década de 1970 debido, en parte, a la ausencia de políticas públicas para abordar esta tendencia. Una explicación es la deriva de las políticas: la desigualdad ha crecido en los EE. UU. Porque el proceso político no ha respondido a las tendencias económicas hacia la desigualdad. Una segunda explicación es la influencia política desigual: los individuos y las corporaciones adinerados ejercen una influencia política superior e inclinan la política pública hacia sus intereses. Comparamos estas explicaciones utilizando el salario mínimo federal y el impuesto mínimo alternativo (AMT) de 1969 a 2012 como casos de comparación. Ambas políticas estaban denominadas en dólares nominales, por lo que el efecto de la inacción de las políticas es comparable para ambos dominios de políticas. Encontramos que (1) era mucho más probable que el Congreso de los Estados Unidos actualizara la política de AMT que la política de salario mínimo después de 1978, (2) el Congreso protegió y aumentó el valor real de la deducción de AMT para las parejas casadas, mientras que el valor real del salario mínimo y la deducción individual disminuyó después de 1978, (3) el Congreso y el Presidente eventualmente convirtieron el AMT — pero no el salario mínimo — en ajustes automáticos por inflación. Estos patrones destacan el papel de la desigualdad política en la formulación de políticas económicas.